OP0123 Prediction of progressive skin thickening in early diffuse systemic sclerosis using three-monthly skin scores from the european scleroderma observational study (ESOS). (15th June 2017) - Herrick, A; Peytrignet, S; Pan, X; Hesselstrand, R; Mouthon, L; Brown, E; Czirják, L; Distler, JH; Distler, O; Fligelstone, K; Gregory, W; Ochiel, R; et al.
Abstract : Background: ESOS (European Scleroderma Observational Study) was a prospective observational study of early diffuse cutaneous systemic sclerosis, recruiting from 50 centres in 19 countries and thus providing a unique opportunity to study parameters of disease progression at regular intervals. Objectives: To describe the characteristics of patients with progressive skin thickening and derive prediction models for progression over 12 months. Methods: Duration of skin thickening and autoantibody status (anti-topoisomerase-1[anti-Scl-70, TOPO], anti-RNA polymerase III[Pol3], anticentromere[ACA]) were documented. The modified Rodnan skin score (mRSS) was recorded 3-monthly for up to two years after baseline. The main outcome was the progression of mRSS. Progressive patients ("progressors") had to meet a 5-unit and 25% increase in their mRSS within the first 12 monthsof follow-up. Features of progressors vs. non-progressors were compared using the Fisher or Kruskal-Wallis test (for categorical and continuous variables), as were progression parameters between autoantibody groups. Logistic models were fitted to predict progression and, using ROC curves, were compared based on AUC, accuracy and positive predictive value (PPV). Results: 326 patients were recruited, with median disease duration of 11.9 months. During the first 12 months, 66 patients (20.3%) progressed, 227 (69.6%) did not and 33 (10.1%) could not have their status assessed. At baseline, progressors had shorter disease duration than non-progressors: 8.1 months vs. 12.6 months (p=0.001). Progressors started with a lower mRSS, median 19 units vs. 21 for non-progressors (p=0.030). 124 patients were TOPO+, 50 were Pol3+, 20 were ACA+, 2 were TOPO+/ACA+ and 68 had none. Pol3+ patients had a higher mRSS peak (35 units vs. 27 overall[p=0.001]) and did so earlier (median 17.9 months vs. 23.1 months overall[p=0.214]). Using an mRSS 22 cutoff point to predict progression in the ESOS cohort (as suggested in the literature) would yield a PPV of 24.3%, a weak improvement from the observed 20.3% share of progressors. A first model (Model A, with mRSS, duration of skin thickening and their interaction) had an accuracy of 60.9%, AUC of 0.67 and PPV of 33.8%. Figure 1 summarizes the prediction rule, with patients under the curved line predicted to progress. By adding a variable for being Pol3+ (Model B), the model reached an accuracy of 71%, AUC of 0.71 and PPV of 41%. Conclusions: Patients with shorter disease duration and a lower mRSS have a higher likelihood of being progressors, with a trade-off between the two. Pol3+ patients experience higher mRSS peaks and tend to reach them earlier. Two prediction models for progressive thickening were derived. The advantage of having two is that Model B, while more accurate and useful in identifying high-risk patients in clinical practice, risks being too restrictive for patient selection into trials and may over-represent Pol3+ patients. Disclosure of Interest: None declared